Spatial Distribution of Io's Neutral Oxygen Cloud Observed by Hisaki. Issue 5 (18th May 2018) - Koga, Ryoichi; Tsuchiya, Fuminori; Kagitani, Masato; Sakanoi, Takeshi; Yoneda, Mizuki; Yoshioka, Kazuo; Yoshikawa, Ichiro; Kimura, Tomoki; Murakami, Go; Yamazaki, Atsushi; Smith, H. Todd; Bagenal, Fran
Abstract: We report on the spatial distribution of a neutral oxygen cloud surrounding Jupiter's moon Io and along Io's orbit observed by the Hisaki satellite. Atomic oxygen and sulfur in Io's atmosphere escape from the exosphere mainly through atmospheric sputtering. Some of the neutral atoms escape from Io's gravitational sphere and form neutral clouds around Jupiter. The extreme ultraviolet spectrograph called EXCEED (Extreme Ultraviolet Spectroscope for Exospheric Dynamics) installed on the Japan Aerospace Exploration Agency's Hisaki satellite observed the Io plasma torus continuously in 2014–2015, and we derived the spatial distribution of atomic oxygen emissions at 130.4 nm. The results show that Io's oxygen cloud is composed of two regions, namely, a dense region near Io and a diffuse region with a longitudinally homogeneous distribution along Io's orbit. The dense region mainly extends on the leading side of Io and inside of Io's orbit. The emissions spread out to 7.6 Jupiter radii ( R J ). Based on Hisaki observations, we estimated the radial distribution of the atomic oxygen number density and oxygen ion source rate. The peak atomic oxygen number density is 80 cm −3, which is spread 1.2 R J in the north‐south direction. We found more oxygen atoms inside Io's orbit than a previous study. We estimated the total oxygen ion source rate to be 410 kg/s, which is consistent with the value derived from a previous study that used a physical chemistry model based on Hisaki observations of ultraviolet emission ions in the Io plasma torus. Key Points: Io's neutral oxygen cloud consists of a leading cloud inside the orbit and a longitudinally uniform region spreading out to 7.6 R J The estimated peak number density of oxygen atoms is 80 cm −3, which is spread 1.2 R J in the north‐south direction The estimated source rate of oxygen ions is 410 kg/s, which is consistent with previous studies